2018
DOI: 10.1016/j.carj.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Error in Abdominal Imaging: Pearls and Pitfalls for Radiologists

Abstract: Peer review for radiologists plays an important role in identifying contributing factors that can lead to diagnostic errors and patient harm. It is essential that all radiologists be aware of the multifactorial causes of diagnostic error in radiology and the methods available to reduce it. This pictorial review provides readers with an overview of common errors that occur in abdominal radiology and strategies to reduce them. This review aims to make readers more aware of pitfalls in abdominal imaging so that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Direct/spot AXRs are mostly used in emergency departments to elucidate the etiology of pain[ 1 , 2 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct/spot AXRs are mostly used in emergency departments to elucidate the etiology of pain[ 1 , 2 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography (USG), magnetic resonance imaging (MRI), computed tomography (CT), and endoscopic interventions are the most commonly used methods. It has been reported that interpretations in diagnostic procedures can be very variable and erroneous reporting (diagnosis) is made in 2%-20% of cases in the literature[ 1 ]. On the other hand, most diagnostic devices, except USG and mobile X-ray devices, can be used with limitations of place, time, device, and technical staff.…”
Section: Introductionmentioning
confidence: 99%